Development of a Literary Learning Model Based on Content Language Integrated Learning (Clil) to Improve Students’ Skills in Literary Appreciation - Asrul, Asrul; Gani, Hamsu Abd.; Mustafa, Mustafa (International Journal of Integrative Sciences, 2024)
This research is Research and Development (P&P) which leads to the development of a Literature Learning Model based on Content Language Integrated Learning (CLIL) to increase literary appreciation in students. The process of developing this learning model goes through four main stages, namely preliminary studies, limited trials and extensive trials and experimental trials. The focus of this research is students of the English Language Education Study Program at Khairun University for class A as a limited trial and class B for a wide trial. The development results show that the CLIL-based literature learning model is valid, practical and effective. Based on the results of the analysis, it shows that the preliminary study stage which includes literature study, field study and preparation of an initial draft of the product which includes planning and developing the design of a Content Language Integrated Learning (CLIL) based Literary Learning model to Increase Student Appreciation of Literature as well as the design of learning tools is categorized as feasible and without revision. Trials with limited samples showed an increase in students' literary appreciation with an average score of 48% in the poor category